Risk factors associated with occurrence of African swine fever outbreaks in smallholder pig farms in four districts along the Uganda-Kenya border - Nantima, Noelina; Ocaido, M.; Ouma, Emily A.; Davies, J.; Dione, Michel M.; Okoth, Edward A.; Mugisha, A.; Bishop, Richard P. (Springer, 2015)
A cross-sectional survey was carried out to assess risk factors associated with occurrence of African swine fever (ASF) outbreaks in smallholder pig farms in four districts along Kenya-Uganda border. Information was collected by administering questionnaires to 642 randomly selected pig households in the study area. The study showed that the major risk factors that influenced ASF occurrence were purchase of pigs in the previous year (p < 0.000) and feeding of pigs with swill (p < 0.024). By employing cluster analysis, three clusters of pig production types were identified based on production characteristics that were found to differ significantly between districts. The most vulnerable cluster to ASF was households with the highest reported number of ASF outbreaks and composed of those that practiced free range at least some of the time. The majority of the households in this cluster were from Busia district in Uganda. On the other hand, the least vulnerable cluster to ASF composed of households that had the least number of pig purchases, minimal swill feeding, and less treatment for internal and external parasites. The largest proportion of households in this cluster was from Busia district Kenya. The study recommended the need to sensitize farmers to adopt proper biosecurity practices such as total confinement of pigs, treatment of swill, isolation of newly purchased pigs for at least 2 weeks, and provision of incentives for farmers to report suspected outbreaks to authorities and rapid confirmation of outbreaks.